The challenges in making electronic health records accessible to patients: Table 1 - Leslie Beard; Rebecca Schein; Dante Morra; Kumanan Wilson; Jennifer Keelan (2011)
It is becoming increasingly apparent that there is a tension between growing consumer demands for access to information and a healthcare system that may not be prepared to meet these demands. Designing an effective solution for this problem will require a thorough understanding of the barriers that now stand in the way of giving patients electronic access to their health data. This paper reviews the following challenges related to the sharing of electronic health records: cost and security concerns, problems in assigning responsibilities and rights among the various players, liability issues and tensions between flexible access to data and flexible access to physicians.